Fibromyalgia syndrome: definition and diagnostic aspects - A. Alciati; G. Arioli; L. Altomonte; R. Casale; G. Cassisi; G. Biasi; M. Spath; D. Buskila; M.A. Giamberardino; R. Torta; F. Marinangeli; F. Salaffi; et al. (PAGEPress Publications, 2011)
Although the term "fibromyalgia" (FM) is relatively new, the condition characterised by chronic musculoskeletal pain that is accompanied by numerous extra-skeletal symptoms has been described in the medical literature for many years under different names. The term "fibrositis," which was originally used in 1904 by Sir William Gowers to define a type of lumbalgia, became a synonym for diffuse musculoskeletal pain until 1976 (1). In the mid-1970s, Smythe and Moldofsky used the term "fibrositic syndrome" to describe the presence of tender points (TPs), sleep disturbances and other accompanying symptoms such as asthenia...